2017
DOI: 10.1038/cddis.2017.478
|View full text |Cite
|
Sign up to set email alerts
|

HSF4 regulates lens fiber cell differentiation by activating p53 and its downstream regulators

Abstract: Cataract refers to opacities of the lens that impede the passage of light. Mutations in heat shock transcription factor 4 (HSF4) have been associated with cataract; however, the mechanisms regarding how mutations in HSF4 cause cataract are still obscure. In this study, we generated an hsf4 knockout zebrafish model using TALEN technology. The mutant zebrafish developed an early-onset cataract with multiple developmental defects in lens. The epithelial cells of the lens were overproliferated, resulting in the ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 58 publications
(103 reference statements)
1
39
0
Order By: Relevance
“…HSF4 is a member of the heat shock transcription factor family that contains conserved DNA binding and trimerization domains (Morimoto, 1993;Nakai et al, 1997). Recent studies showed that HSF4 is expressed in many tissues and is required for mammalian cellular proliferation and differentiation (Min et al, 2004;Mitsuaki et al, 2004;Gao et al, 2017). Notably, Jin et al (2012) observed HSF4 is positively involved in tumorigenesis that is induced following disruption of the p53 gene.…”
Section: Discussionmentioning
confidence: 99%
“…HSF4 is a member of the heat shock transcription factor family that contains conserved DNA binding and trimerization domains (Morimoto, 1993;Nakai et al, 1997). Recent studies showed that HSF4 is expressed in many tissues and is required for mammalian cellular proliferation and differentiation (Min et al, 2004;Mitsuaki et al, 2004;Gao et al, 2017). Notably, Jin et al (2012) observed HSF4 is positively involved in tumorigenesis that is induced following disruption of the p53 gene.…”
Section: Discussionmentioning
confidence: 99%
“…shRNA transfection was conducted according to the previous studies 14,21 . Briefly, HCC cells were seeded in a 6‐well plate.…”
Section: Methodsmentioning
confidence: 99%
“…Heat shock transcription factors (HSFs) play an important role in regulating heat shock proteins expression, and HSFs have been reported to be a critical regulator of many vital physiological processes such as proteotoxic stresses protection and inflammation 12‐14 . Heat shock factor 4, which contains conserved DNA binding and trimerization domains, is a vital member of HSFs.…”
Section: Introductionmentioning
confidence: 99%
“…(Cvekl and Zhang, 2017) Pathogenic variations or knockdown of genes implicated in human cataract and/or deafness in zebrafish have been shown to recapitulate similar phenotypes. (Gao et al, 2017;Mishra et al, 2018;Yousaf et al, 2018;Takamiya et al, 2016;Busch-Nentwich, 2004) Using two strategies (morpholino and CRISPR/Cas9) the fish developed a cataract and ear phenotype that could be rescued. We did not observe other obvious anomalies.…”
Section: Discussionmentioning
confidence: 99%